Structure, Properties and Applications of Polymeric Foams - Hejna, Aleksander (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Foaming of polymeric materials enables weight reduction, which is very important from the economic point of view, but most of all, it should be considered as an excellent means to provide new properties to various polymeric materials. Permanent developments in foaming technologies allow manufacturing of foams with micro- and even nano-sized pores, expanding the already very wide range of their applications. Except for the most conventional applications, which include damping materials, thermal and acoustic insulation, packaging materials or absorbents, applications in catalysis, fuel cells, tissue engineering, and electromagnetic shielding, often associated with nanocellular structures, have become more and more popular.Moreover, having in mind the ongoing trends and law regulations, it is important to remember the environmental impact of polymeric foams. Recent technological developments often involve biodegradability of foams, application of environmentally friendly raw materials, and innovative recycling methods.Because of the richness of potential innovations and future developments, the Editors are pleased to present the Structure, Properties and Applications of Polymeric Foams book, a collection of papers from Materials Special Issue dealing with the structure, performance, and applications of polymeric foams.